Principles of Entrepreneurship (ENT530): Social Media Portfolio: Clicyca.co / Nurdarwisyah Balqis Dzuladin - Dzuladin, Nurdarwisyah Balqis (2021)
Clicyca.co is a brand of NDBD PRODUCTION and own my Nurdarwisyah Balqis Dzuladin. This brand serves a handmade and local product with creativity and freedom ideas. Special for gift, anniversary gift, birthday gift, friendship gift, siblings gift and best friend gift. Other than that, the 3 main product are mug, doodling frame and mini bookmarks. The speaciality of the brand are all the product inspired from doodles either in colourful or its only black and white doodle.